HUBUNGAN ANTARA LINGKAR PINGGANG DENGAN KADAR ALBUMIN URIN PRIA DEWASA DENGAN OBESITAS SENTRAL - Biasa, Christie Endrio; Moeis, Emma Sy.; Waleleng, B. J. (e-CliniC, 2014)
Abstract: Obesity is an abnormal accumulation of body fat in proportion to body size. Central obesity is a major problem in clinical and public health. Central obesity is closely related to metabolic risk factors such as insulin-resistant,Â hypertension, and dyslipidemia. Obesity can lead to functional and structural changes in the kidneys. Reduced insulin sensitivity is the most important link between obesity and other metabolic complications cause kidney injury. Insulin also increases the effect of angiotensin II on mesangial cells, thus contributing to hypertension, increased intraglomerular pressure, exacerbation of proteinuria, intrarenal induction of inflammatory cytokines and growth factors and apoptosis. Microalbuminuria is one of the first indicators of kidney abnormalities and has been used to detect problems in kidney function. Methods: this study uses an analytical method with cross-sectional study. By looking at the relationship betwen urinary albumin with waist circumference in men with central obesity. Results: respondents waist circumference (central obesity with waist circumference> 90 cm) with a urine albumin levels. 30 samples consisting of students and staff in the Faculty of Medicine Unsrat. This research was carried out not by checking the dipstick albumin as less sensitive, but using the ratio of albumin to creatinine examination. The results showed no significant association between waist circumference and urinary albumin levels. Conclusion: although the results of the study showed no significant association between waist circumference and levels of albuminuria, but not eliminate the risk of central obesity to kidney disorders. Keywords: obesity, central obesity, urine albumin levels. Â Abstrak: Obesitas adalah akumulasi abnormal lemak tubuh dalam proporsi ukuran tubuh. Obesitas sentral adalah masalah utama secara klinik dan kesehatan masyarakat. Obesitas sentral sangat berhubungan dengan faktor-faktor resiko metabolik seperti resitensi insulin, hipertensi, dan dislipidemia. Obesitas dapat menyebabkan perubahan fungsional dan struktural pada ginjal. Sensitivitas insulin berkurang merupakan rantai penghubung yang paling penting antara obesitas dan komplikasi metabolik lainnya menyebabkan cedera ginjal. Insulin juga meningkatkan efek angiotensin II pada sel mesangial, sehingga memberikan kontribusi untuk hipertensi, peningkatan tekanan intraglomerular, eksaserbasi proteinuria, induksi sitokin inflamasi intrarenal dan faktor-faktor pertumbuhan dan apoptosis. Mikroalbuminuria adalah salah satu indikator pertama dari abnormalitas ginjal dan telah digunakan untuk mendeteksi masalah pada fungsi ginjal. Metode: penelitian ini menggunakan metode analitik dengan studi cross-sectional. Dengan melihat hubungan kadar albumin urin dengan lingkar pinggang pada pria dengan obesitas sentral. Hasil: lingkar pinggang responden (obesitas sentral dengan lingkar pinggang >90 cm) dengan kadar albumin urine. 30 sampel yang terdiri dari mahasiswa dan pegawai di Fakultas Kedokteran Unsrat. Penelitian ini dilakukan bukan dengan pemeriksaan dipstick albumin karena kurang sensitif, tapi menggunakan pemeriksaan rasio albumin terhadap kreatinin. Hasil yang diperoleh menunjukkan tidak ada hubungan yang signifikan antara lingkar pinggang dengan kadar albumin urine. Simpulan: walaupun hasil penelitian tidak menunjukkan adanya hubungan signifikan antara lingkar pinggang dengan kadar albuminuria, namun tidakÂ menghilangkan resiko obesitas sentral terhadap gangguan ginjal. Kata kunci: obesitas, obesitas sentral, kadar albumin urine.